Agricultural Pesticide Residue Levels in Soil from the farms Along Thiba River Catchment Area, Mwea Irrigation Scheme, Kirinyaga County, Kenya - Deborah A. Abong’o,; Victor K. Korir,; Joyce G.N. Kithure,; Vincent O. Madadi, (International Journal of Scientific Research in Science and Technology, 2024)
The study assessed the agricultural pesticide residue levels in soil samples from six selected sites along Thiba River catchment area, Mwea Irrigation Scheme, Kirinyaga County, Kenya. The aim was to determine pesticide residue levels in the dry and wet seasons of the year and compare to the set limits by the World Health Organization (WHO). The soil samples were collected in February and May 2021 representing the dry and wet seasons respectively, according to the meteorological department in Kenya and based on the human activities and crops grown in the study area. Chlorpyrifos was the most prevalent pesticide residue detected with levels ranging from 7.38±1.04µg/kg - 213.43±34.75 µg/kg; Lambda- cyhalothrin’s from < 0.005 µg/kg- 13.98 ± 2.02 µg/kg while the levels of Metalaxyl residue ranged from < 0.05 µg/kg - 6.88±0.55 µg/kg in dry and wet seasons. The pesticide residue levels were higher in soil samples in the dry than the wet season. Metalaxyl and Lambda-cyhalothrin residue levels were lower than the set Maximum Residue Levels in soil by the WHO of 50 µg/kg and 20 µg/kg in the dry and wet seasons respectively. The chlorpyrifos pesticide residue levels were higher than the set limits of 10 µg/kg by the WHO except in sites 5 and 6 (upstream) in both the dry and wet seasons.
Keywords: Chlorpyrifos; Lambda cyhalothrin; Metalaxyl; Residue levels; Mwea Irrigation Scheme; Thiba River; soil; Kirinyaga County